Re‐evaluation of physical interaction between plant peroxisomes and other organelles using live‐cell imaging techniques. Issue 7 (17th May 2019) - Oikawa, Kazusato; Hayashi, Makoto; Hayashi, Yasuko; Nishimura, Mikio
Abstract: The dynamic behavior of organelles is essential for plant survival under various environmental conditions. Plant organelles, with various functions, migrate along actin filaments and contact other types of organelles, leading to physical interactions at a specific site called the membrane contact site. Recent studies have revealed the importance of physical interactions in maintaining efficient metabolite flow between organelles. In this review, we first summarize peroxisome function under different environmental conditions and growth stages to understand organelle interactions. We then discuss current knowledge regarding the interactions between peroxisome and other organelles, i.e., the oil bodies, chloroplast, and mitochondria from the perspective of metabolic and physiological regulation, with reference to various organelle interactions and techniques for estimating organelle interactions occurring in plant cells. Abstract : Physical interactions between organelles are important in maintaining efficient metabolite flow between these organelles. In this review, we summarize peroxisome function under different environmental conditions and growth stages to understand organelle interactions. We then discuss current knowledge regarding the interactions between peroxisome and other organelles, i.e., the oil bodies, chloroplast, and mitochondria.